The devil and Mrs. Davenport : a novel - Kennedy, Paulette (Seattle : Lake Union Publishing, 2024)
"Missouri, 1955. Loretta Davenport has led an isolated life as a young mother and a wife to Pete, an ambitious assistant professor at a Bible college. They're the picture of domestic tranquility-until a local girl is murdered and Loretta begins receiving messages from beyond. Pete dismisses them as delusions of a fevered female imagination. Loretta knows they're real-and frightening. Defying Pete's demands, Loretta finds an encouraging supporter in parapsychologist Dr. Curtis Hansen. He sees a woman with a rare gift, more blessing than curse. With Dr. Hansen's help, Loretta's life opens up to an empowering new purpose. But for Pete, the God-fearing image he's worked so hard to cultivate is under threat. No longer in control of his dutiful wife, he sees the Devil at work. As Loretta's powers grow stronger and the pleading spirits beckon, Pete is determined to deliver his wife from evil. To solve the mysteries of the dead, Loretta must first save herself"--
Includes discussion questions.
Keywords: Housewives -- Fiction; College teachers -- Fiction; Married people -- Fiction; Murder -- Fiction; Psychic ability -- Fiction; Parapsychologists -- Fiction; Faith (Christianity) -- Fiction; Missouri -- Fiction; Gothic fiction; Historical fiction